Two new records of the fern genus Coniogramme (Pteridaceae) from Vietnam - Wang, Caihong (PhytoKeys, 2019)
Abstract. Two new records of the fern genus Coniogramme Fée from Vietnam, C.japonica and C.procera, are presented. In addition, a key to recognising the species of Coniogramme in Vietnam is given in this paper.